DETERMINATION OF SHARIA FINANCING SCHEMES IN THE MARINE AND FISHERIES SECTOR IN MALUKU - Shalihah, Mar'atun; Deny Yarusain Amin; Mohammad H. Holle; Gadissifah A. Nur Bella (Al-Muhasib: Journal of Islamic Accounting and Finance, 2024)
This study aims to identify and determine an appropriate Sharia-compliant financing scheme that meets the needs of the marine and fisheries sector in Maluku. Given this sector's significant potential to support the regional economy, it still faces challenges in accessing financing. The study uses the Analytic Hierarchy Process (AHP) and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). The analysis results indicate that the five main criteria in selecting Sharia financing schemes are profitability, risk, Sharia compliance, accessibility, and social impact. Through TOPSIS, mudharabah and musyarakah financing schemes were identified as the best alternatives meeting these criteria. The study also found that business actors in Maluku’s marine and fisheries sector still require improved financial literacy in Sharia finance to fully leverage existing financing opportunities. Sharia financing schemes such as qardh hasan and ijarah are also deemed essential, especially to support small and medium enterprises (SMEs) needing low-risk capital access. This study is expected to contribute to the development of the marine and fisheries sector in Maluku by promoting more effective and sustainable use of Sharia-compliant financing schemes.